IMPLEMENTASI KEBIJAKAN PENGADAAN TANAH BAGI PELAKSANAAN PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Kaja, Kaja (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
The land acquisition policy for development purposes in the public interest in Bukit Segaloh Village is carried out through purchase or other terms of compensation for land ownership surrendered by the owner for development without coercion and is done consciously based on an agreement so that no issues arise. The research aims to analyze how the implementation of land acquisition policy in Indonesia, the challenges faced, and the solutions that can be offered to realize justice and efficiency in development implementation. The research objective is to analyze the implementation of land acquisition policy for development purposes in the public interest and the challenges faced, as well as solutions that can be offered to realize justice and efficiency in development implementation. The land acquisition procedure has been carried out through the surrender of land rights and sale-purchase agreed upon by the parties concerned. The land surrendered still uses a land certificate (SKT), granting land rights controlled directly by the state to one or several people jointly or a legal entity. The landowner does not determine the amount of compensation but is based on an agreement. The agreement is made considering the limited budget for land acquisition and the source of funds used by policymakers for land acquisition. Implementation of policies related to land acquisition has been carried out through coordination, communication, and mutual agreement.